Successful projects or success in project management - are projects dependent on a methodology? - Henrik J. Nyman; Anssi Öörni (International Journal of Information Systems and Project Management, 2023)
The purpose of this paper is to bridge two seemingly disparate views of project management: proponents of project management methodologies promote a view where a standard set of predefined project practices guarantee project success, while a contingent view of projects suggests that project management needs to be adaptive to project actuality and context. Our aim in this paper is to understand how these different forms of managing projects impact project success. We investigate projects through a lens of discretion, defined as autonomy in the project team to adapt the project to its context as opposed to a reliance on a pre-defined set of rules for project management. We also look at the role of exploration, that is, whether the project focuses on the development of new knowledge, or whether the focus is on furthering existing competences. Based on our analysis, we propose a framework to determine the right amount of discretion in a project, highlighting which project management methodology is suited for the work at hand or whether discarding methodology altogether is more likely to lead to project success.